Accuracy assessment of Precise Point Positioning with multi-constellation GNSS data under ionospheric scintillation effects - Marques, Haroldo Antonio; Marques, Heloisa Alves Silva; Aquino, Marcio; Vadakke Veettil, Sreeja (EDP Sciences, 2018)
GPS and GLONASS are currently the Global Navigation Satellite Systems (GNSS) with full 16 operational capacity. The integration of GPS, GLONASS and future GNSS constellations can 17 provide better accuracy and more reliability in geodetic positioning, in particular for kinematic 18 Precise Point Positioning (PPP), where the satellite geometry is considered a limiting factor to 19 achieve centimeter accuracy. The satellite geometry can change suddenly in kinematic 20 positioning in urban areas or under conditions of strong atmospheric effects such as for instance 21 ionospheric scintillation that may degrade satellite signal quality, causing cycle slips and even 22 loss of lock. Scintillation is caused by small scale irregularities in the ionosphere and is 23 characterized by rapid changes in amplitude and phase of the signal, which are more severe in 24 equatorial and high latitudes geomagnetic regions. In this work, geodetic positioning through the 25 PPP method was evaluated with integrated GPS and GLONASS data collected in the equatorial 26 region under varied scintillation conditions. The GNSS data were processed in kinematic PPP 27 mode and the analyses show accuracy improvements of up to 60% under conditions of strong 28 scintillation when using multi-constellation data instead of GPS data alone. The concepts and 29 analyses related to the ionospheric scintillation effects, the mathematical model involved in PPP 30 with GPS and GLONASS data integration as well as accuracy assessment with data collected 31 under ionospheric scintillation effects are presented.